(3JSdjc GdfaS Edi MXjQI GdbOSs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdCRdj(B... (3CeG HYO abO CLHJ SDGdc CjgG GdhdO GdUGdM eMeO(B... (3Ydi GdeSGFd GdegeI GdTQjaI hGdfcJ GdYXjeI GddWjaI(B...s
(3BNQgG (B:s
(3hGdeYJRdI bGdhG(B: (3CUhd GdEjeGf NeSI; GdJhMjO hGdUdGI hGdfHhI(B... (3hdjcf gPG BNQ eG bUOfG EKHGJg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B286s
(3GdPQjYI, Qbe(B: 889s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds